The Influence of Parents' Socio-Economic Status, Motivation, Self-Efficacy, Teacher-Student Interactions on Interest in Entering Higher Students - Tumpak Simangunsong; H. Suwatno (Green Publisher Indonesia, 2026)
Education is a crucial asset for the development of society and the nation. However, the low percentage of individuals pursuing higher education in Indonesia remains a concern that requires further investigation. Various factors influence students’ decisions not to continue their education at the tertiary level. This study aims to analyze the influence of parents’ socioeconomic status, self-efficacy, motivation, and academic achievement on students’ interest in pursuing higher education. The research adopted a quantitative approach, with data collected from 48 Social Sciences students at Cimindi Adventist High School. Causal relationships were analyzed using multiple linear regression analysis. The findings indicate that parents’ socioeconomic status, self-efficacy, motivation, and academic achievement have a significant positive effect on students’ interest in continuing their education. These results emphasize the importance of teachers and school management in consistently enhancing student motivation and self-efficacy, particularly for students from lower socioeconomic backgrounds, to encourage continued engagement in higher education. Participation in higher education is strongly influenced by factors such as parents’ socioeconomic status, motivation, self-efficacy, and academic achievement. Therefore, it is crucial for schools and educators to provide adequate support, especially to students from low-income backgrounds, to motivate them to pursue higher education.